El Banquete de Platón: Eros y la composición del discurso de Aristófanes - Esteban Santos, Alicia (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2010)
This paper is fi rst focussed on the respective «frames» (beginnings and ends) of the several Plato’s Symposium’s discourses, with strong eulogy of Eros, very emphasized by means of all kind of resources, Ringkomposition especially, in the fi rst fi ve speeches. But in Socrates-Diotima’ discourse the composition is different, although very elaborate also: a complex structure of concentric circles or frames, with the essential in the centre, the Beauty or the Goodness itself. On the other hand, we analyse more carefully Aristophanes’ speech (189d-193d), regarding the form and the content, and we appreciate that is a rounded work in itself and that shows signifi cant points of contact with Socrates-Diotima’ speech: Love leads to the One, to the Good.